Why the Emergency Department Visit Decreased during the Covid-19 Pandemic? Case Study in Hospital, Malang Regency - Kusumawati, Anita Mardiana; Widyaningrum, Kurnia (Jurnal Kedokteran Brawijaya, 2021)
During the 2020 Covid-19 pandemic, emergency department experienced a drastic decreasing visit that could disrupt hospital financing. This study was conducted to identify the root cause of the declining ED visit. The study was conducted descriptively from FGD involving eight selected respondents, surveys on 83 patients regarding service perceptions and satisfaction, as well as secondary data on visits and requests of discharge against medical advice. The results showed that the decreasing visit was due to the patient's refusal on treatment in the isolation room, the staff's skills to provide communication and education, and the potential of cooperation termination from partners. Those refusals were due to the patient's perception of hospital services and the differences in patient needs on health protocols resulted from the lack of individual and organizational communication. Hospitals need to build staff's skills in communication and education as well as intensive communication strategies with partners to communicate policies and service system changes so that trust and a positive image are built.